Improvement of Symmetrical Gait Index in People with Chronic Stroke - Sonthikul, Chatwalai; Bovonsunthonchai, Sunee; Tretriluxana, Jarugool; Bunprajan, Tipwadee (Naresuan University Journal: Science and Technology (NUJST), 2016)
Objective: To compare the effect of the forward and the backward partial body weight support (PBWS) treadmill training on gait symmetrical index (SI) in people with chronic stroke. Methods: Twenty people with chronic stroke were allocated into two groups; the forward (n = 10) and the backward (n = 10) PBWS treadmill training groups. Participants in both groups were matched by age range and severity score assessing by the Brunnstrom stage. They received the training program for 80 minutes over at least 2 sessions per week for 12 sessions. The program consisted of 60 minutes of the conventional physical therapy treatment and 20 minutes of the treadmill training (backward or forward). Gait SI variables were assessed and were compared within and between groups. Results: For within group comparisons, the forward PBWS treadmill training showed significant differences of the step length symmetry ( p -value = 0.009) and the single support time symmetry ( p -value = 0.037) between pre- and post-training. Whereas, no significant difference of any gait SI variables was found between pre- and post-training in the backward PBWS treadmill training group. In between groups comparison, participants in the forward PBWS treadmill training group showed greater walking improvement than those of the backward PBWS treadmill training group in step length symmetry ( p -value=0.019). While, participants in the backward PBWS treadmill training group showed greater improvement than those of the forward PBWS treadmill training group in the step time symmetry ( p -value = 0.049). Conclusions: After 12 sessions of training, the forward PBWS treadmill training group showed significant improvement in the step length symmetry and the single support time symmetry. Whereas, the backward PBWS treadmill training group show no significant improvement in all gait SI. When compare difference between groups, the forward PBWS treadmill training group showed greater improvement than those of the backward PBWS treadmill training group in the step length symmetry. Whereas, the backward PBWS treadmill training group showed greater improvement than those of the forward PBWS treadmill training group in the step time symmetry. Keywords : Stroke, Forward walking, Backward walking, Treadmill training with partial body weight support, Gait asymmetry
Keywords: Stroke, Forward walking, Backward walking, Treadmill training with partial body weight support, Gait asymmetry